Spatio-temporal dynamics of ichthyoplankton in the Kowie estuary, South Africa - Kruger, Michelle (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2010)
Ichthyoplankton dynamics in the permanently open Kowie Estuary, in the warm temperate region of South Africa was investigated. The composition, abundance, distribution and seasonality of larval fishes were studied over a two year period between 2004 and 2006. Additionally, tidal exchange of ichthyoplankton and the use of frontal zones in the mouth region of the estuary were also explored between 2008 and 2009. Temporal and spatial trends in occurrence of larval fishes within the estuary and associated marina were obtained from data collected seasonally using boat-based plankton netting at 14 sampling stations along the length of the estuary. A total of 11 128 larval fishes were collected, representing 23 families and 38 taxa. Clupeidae and Gobiidae were the dominant fish families, contributing 47.0 % and 24.7 % respectively to the total catch. Estuarine resident species dominated the overall catch (91 %). A notable absence of older stage larvae and early juveniles characterised the artificial channels of the marina and estuary mouth region. This was attributed to the absence of a shallow, marginal water habitat typical of successful estuarine nursery areas. Tidal exchange of larval fishes was investigated in the Kowie Estuary using a new technique. A set of drifting light traps were set repetitively on the ebb and flood tide every second night for two consecutive 14 day periods during the peak estuarine recruitment period. A total of 553 larval fishes were caught during the study, representing nine families and 26 species. Blenniidae and Clupeidae dominated the catches. Family and species occurrence changed with tide state. Species richness (d) and diversity (H') varied with tide and was highest on flood tides. Estuary-dependent species, such as Omobranchus woodii were more dominant on flood tides, whilst larvae of marine-spawned species, such as Sardinops sagax, were dominant on the ebb tide. Light trap catches yielded a different composition in terms of development stage / size and species, when compared to towed net studies. Towed plankton nets were again used to study the shear fronts that characterise the mouth region of the canalised Kowie Estuary. It was hypothesised that the convergence zone of the front provides feeding opportunities for ichthyoplankton. Ichthyoplankton, zooplankton and phytoplankton was collected from within and immediately outside of the convergence zone during frontal conditions. Species specific distribution trends emerged from this study. Postflexion larvae and early juvenile stages of the estuary dependent Mugilidae were only present in the foam line of the convergence zones. Some known predators of ichthyoplankton were also present in slightly higher numbers in the convergence zone (isopods) while other predators such as mysid shrimps, chaetognaths and cnidarians were more abundant out of the convergence zone. It appears that these zones may provide access to temporary food patches in the lower estuary but will be accompanied by a trade-off with increased isopod predators. The Kowie Estuary is a heavily impacted system and lack of adequate freshwater supply; artificial channelling and pollution ultimately have a negative impact of the success of this system as a nursery area. Rehabilitation of marginal areas in the lower estuary and marina is suggested as remedial action to re-establish the integrity of the nursery function this system could offer.
Keywords: Fishes -- Larvae -- South Africa -- Port Alfred; Estuarine fishes -- South Africa -- Port Alfred